A systematic review of literature on contested heritage. Issue 4 (16th February 2021) - Liu, Yang; Dupre, Karine; Jin, Xin
ABSTRACT: Contested heritage has increasingly been studied by scholars over the last two decades in multiple disciplines, however, there is still limited knowledge about what contested heritage is and how it is realized in society. Therefore, the purpose of this paper is to produce a systematic literature review on this topic to provide a holistic understanding of contested heritage, and delineate its current state, trends and gaps. Methodologically, four electronic databases were searched, and 102 journal articles published before 2020 were extracted. A content analysis of each article was then conducted to identify key themes and variables for classification. Findings show that while its research often lacks theoretical underpinnings, contested heritage is marked by its diversity and complexity as it becomes a global issue for both tourism and urbanization. By presenting a holistic understanding of contested heritage, this review offers an extensive investigation of the topic area to help move literature pertaining contested heritage forward.